Community policing: international patterns and comparative perspectives - Wisler, Dominique; Onwudiwe, Ihekwoaba D. (Advances in police theory and practice series)
Rethinking Police and Society: Community Policing in ComparisonD. Wisler and I. D. OnwudiweCommunity Policing in a High Crime Transitional State: The Case of South Africa Since Democratization in 1994 A. MinnaarReforming Community, Reclaiming the State: The Development of Sungusungu in Northern TanzaniaS. HealdCommunity Policing: The Case of Informal Policing in Nigeria I. D. OnwudiweThe French Centralized Model of Policing: Control of the Citizens C. MouhannaCommunity Policing in Belgium: The Vicissitudes of the Development of a Police Model S. Smeets and C. TangePatterns of Community Policin